2019
DOI: 10.5306/wjco.v10.i2.52
|View full text |Cite
|
Sign up to set email alerts
|

Existing anti-angiogenic therapeutic strategies for patients with metastatic colorectal cancer progressing following first-line bevacizumab-based therapy

Abstract: Continuous inhibition of angiogenesis beyond progression is an emerging treatment concept in the management of metastatic colorectal cancer patients with prior bevacizumab exposure. Treatment options include the continuation or reintroduction of bevacizumab during the second-line chemotherapy or switching to a different antiangiogenic monoclonal antibody such as aflibercept or ramucirumab. In the selection of treatment, patient-based factors such as performance status, age, tumor burden, and tolerance and sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Ramucirumab, an antiangiogenic agent, is a human immunoglobulin G1 monoclonal antibody receptor antagonist of vascular endothelial growth factor receptor 2 . Several phase III studies have shown that the addition of ramucirumab to a chemotherapy regimen improves the overall survival of patients with gastric cancer, gastroesophageal junction adenocarcinoma, and colorectal cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Ramucirumab, an antiangiogenic agent, is a human immunoglobulin G1 monoclonal antibody receptor antagonist of vascular endothelial growth factor receptor 2 . Several phase III studies have shown that the addition of ramucirumab to a chemotherapy regimen improves the overall survival of patients with gastric cancer, gastroesophageal junction adenocarcinoma, and colorectal cancers .…”
Section: Discussionmentioning
confidence: 99%
“…This causes a conformational change that prevents the binding of the VEGFR ligands VEGF‐A, VEGF‐C, and VEGF‐D. These ligands are secreted by solid tumors to promote angiogenesis 51 . Ramucirumab was approved by the FDA in 2015 to treat metastatic CRC in patients that had experienced disease progression on or after prior therapy with bevacizumab, oxaliplatin, and 5‐FU/capecitabine.…”
Section: Targeted Therapeuticsmentioning
confidence: 99%
“…For anti-cancer activity xenograft model, a total of 24 six-week-old nude mice (National Laboratory Animal Center (NLAC), Taipei, Taiwan) were injected subcutaneously with the same volume of Matrigel (BD bioscience, San Jose, California, USA), and 1×10 7 of HCT-116 cells into the right ank of each animal. When tumors had grown to around 300 mm 3 , the treatment started. Tumor size was measured twice weekly and calculated from V = length* width 2 /2.…”
Section: In Vivo Animal Modelsmentioning
confidence: 99%